1999
DOI: 10.1159/000031080
|View full text |Cite
|
Sign up to set email alerts
|

The French Haemovigilance System

Abstract: Haemovigilance is a national system of surveillance and alarm, from blood collection to the follow–up of the recipients, gathering and analysing all untoward effects of blood transfusion in order to correct their cause and prevent recurrence. In France haemovigilance was created by law and notification of transfusion incidents is a legal obligation. The haemovigilance network associates local correspondents in each hospital and blood centre with regional co–ordinators and is centralised by the Agence Française… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 0 publications
0
18
0
2
Order By: Relevance
“…In the United States during the time‐period 1986–91, bacterial contamination accounted for 15·9% of all transfusion‐related fatalities [1]. From 1994 to March 1998, the French Blood Agency Haemovigilance surveillance system attributed 18 deaths (four occurring in 1997) to blood components contaminated with bacteria [2,3]. Bacterial transfusion transmission was reported to the Haemovigilance surveillance system as the most frequently identifiable cause of death [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States during the time‐period 1986–91, bacterial contamination accounted for 15·9% of all transfusion‐related fatalities [1]. From 1994 to March 1998, the French Blood Agency Haemovigilance surveillance system attributed 18 deaths (four occurring in 1997) to blood components contaminated with bacteria [2,3]. Bacterial transfusion transmission was reported to the Haemovigilance surveillance system as the most frequently identifiable cause of death [3].…”
Section: Introductionmentioning
confidence: 99%
“…From 1994 to March 1998, the French Blood Agency Haemovigilance surveillance system attributed 18 deaths (four occurring in 1997) to blood components contaminated with bacteria [2,3]. Bacterial transfusion transmission was reported to the Haemovigilance surveillance system as the most frequently identifiable cause of death [3]. In the UK, the Serious Hazards of Transfusion (SHOT) surveillance system reported that of 26 transfusion‐transmitted infections in 1995–2000, 15 were caused by bacteria [4].…”
Section: Introductionmentioning
confidence: 99%
“…blood components transfused every year. [11][12][13][14][15][16] In the UK where haemovigilance is a national scheme between professionals (SHOT, Serious Hazards of Transfusion), on a voluntary basis, covering transfusion reactions of grades 2-4, the number of notifications is much lower than in France. In 1996/1997 there have [17][18][19][20][21][22] In all, 55% of the reports fell into the category 'wrong blood to wrong patient' or IBCT (independently of the presence or absence of clinical signs).…”
Section: Some Longitudinal Results From Existing Surveillance Systemsmentioning
confidence: 99%
“…National haemovigilance schemes to monitor adverse transfusion events have been introduced in many countries, 4 7 8 and EU-wide data are being collated by the European Haemovigilance Network. Similar systems exist in the United States and Canada.…”
Section: Measures To Reduce the Risk Of Transfusing Variant Creutzfelmentioning
confidence: 99%
“…8 9 Most are senior nurses, but some are doctors or biomedical scientists. These posts have been created to implement recommended policies to reduce inappropriate prescribing of blood components 20.…”
Section: Appointment Of Specialist Transfusion Practitionersmentioning
confidence: 99%